Melatonin reduces experimental subarachnoid hemorrhage-induced oxidative brain damage and neurological symptoms - (:unkn) unknown (WILEY, 2009)
Oxidative stress has detrimental effects in several models of neurodegenerative diseases, including subarachnoid hemorrhage (SAH). This study investigated the putative neuroprotective effect of melatonin, a powerful antioxidant, in a rat model of SAH. Male Wistar albino rats were divided as control, vehicle-treated SAH, and melatonin-treated (10 mg/kg, i.p.) SAH groups. To induce SAH, 0.3 mL blood was injected into cisterna magna of rats. Forty-eight hours after SAH induction, neurological examination scores were measured and the rats were decapitated. Brain tissue samples were taken for blood-brain barrier (BBB) permeability, brain water content, histological examination, or determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO), and Na+-K+-ATPase activities. Formation of reactive oxygen species in brain tissue samples was monitored by using a chemiluminescence (CL) technique. The neurological examination scores were increased in SAH groups on the second day of SAH induction and SAH caused a significant decrease in brain GSH content and Na+-K+-ATPase activity, which was accompanied with significant increases in CL, MDA levels, and MPO activity. On the other hand, melatonin treatment reversed all these biochemical indices as well as SAH-induced histopathological alterations, while increased brain water content and impaired BBB were also reversed by melatonin treatment. This study suggests that melatonin, which can easily cross BBB, alleviates SAH-induced oxidative stress and exerts neuroprotection by preserving BBB permeability and by reducing brain edema.
Keywords: antioxidant; lipid peroxidation; melatonin; subarachnoid hemorrhage; CEREBRAL-ARTERY OCCLUSION; NITRIC-OXIDE; BARRIER PERMEABILITY; REACTIVE OXYGEN; RADICAL SCAVENGER; DOUBLE-BLIND; VASOSPASM; INJURY; RAT; MODEL